Nicotine Exerts a Stronger Immunosuppressive Effect Than Its Structural Analogs and Regulates Experimental Colitis in Rats - Kohki Okada; Kano Matsuo (Biomedicines, 2023)
Ulcerative colitis (UC) is an intractable disease that causes persistent colonic inflammation. Numerous studies have reported that smoking can afford clinical benefits in UC. This study aimed to elucidate whether nicotine, the main component in cigarettes, can exert pharmacological effects against experimental UC. To achieve this objective, we compared the effects of nicotine with those of structural nicotine analogs in a UC rodent model (Slc: Wistar rats, male, 9-week-old, and 220–250 g/rat). Nicotine, or a respective structural analog (nornicotine, cotinine, anabasine, myosmine, and anatabine), was administered intraperitoneally daily to rats (n = 6/group) exhibiting dextran sulfate sodium-induced experimental colitis. Examining the colon tissues of model rats, we compared disease severity, cytokine secretion, and α7 nicotine acetylcholine receptor (nAChR7) expression. We observed that nicotine administration induced weight loss at 2.35% in 10 days. Notably, the reduction in histological severity (score) of UC was more pronounced in rats treated with nicotine (score = 4.83, p = 0.042) than in untreated rats (score = 8.17). Nicotine administration increased nAChR7 expression 6.88-fold (p = 0.022) in inflammatory sites of the colon, mainly by suppressing the production of interleukin (IL)-1β and IL-6. Moreover, the secretion of these cytokines was suppressed in lipopolysaccharide-stimulated rat macrophages (MΦ) treated with nicotine. In conclusion, nicotine better alleviates experimental UC than the examined structural analogs by activating nAChR7 expression and suppressing proinflammatory cytokines in MΦ.